Hotel Magnezit - Tarr, Béla 1955- (Artificial eye, 2012)
"Documentary about a hostel for workers. An old worker suspected of stealing a motor gets fired from the factory and must leave the hostel." [imdb.com]
Original: Ungarn 1978
Bildformat 1.37:1
Keywords: Film; DVD-Video